Perspectives on pharmacologic strategies in the management of meningoencephalomyelitis of unknown origin in dogs - Beasley, Michaela J.; Shores, Andy (Frontiers in Veterinary Science, 2023)
There are many non-infectious inflammatory diseases, assumed to be immune-mediated in origin, recognized to affect the nervous system in canine patients. Concentrating on meningoencephalomyelitis of unknown origin, we will discuss the medications used to treat the underlying disease process, focusing on their adverse effects, therapeutic monitoring when necessary and effectiveness. The literature overwhelmingly supports the use of a steroid/ Cytosar® or steroid/ cyclosporine treatment protocol with the steroid tapered after the acute phase of the disease, leaving the secondary medication to control the disease long term. The decision on when and how quickly to taper the steroid is clinician dependent as a best practices has not been established in the literature. Also discussed will be the supportive care treatments often needed in the acute phase of these patients’ diagnosis and treatment such as anti-edema and anti-epileptic agents.